Importance of winter pea cv. Maksimirski rani in milk production on family farms - Darko Uher; Zvonimir Štafa; Mihaela Blažinkov; Ana Pisačić; Martina Kmet; Maja Ščavničar (Mljekarstvo, 2010)
Forage pea (Pisum sativum L.) is gaining importance as a forage legume in the Republic of Croatia. Pea seed contains 20-30 percent of protein, it is utilized without thermal treatment in feeding different types and categories of livestock, and with stable yield it provides an appreciable income per hectare. Two-year field trials (2005-2006) were carried out to determine the effect of winter pea seed inoculation and nitrogen top-dressing on the number and mass (g/plant-1) of root nodules and also on the yield and quality of winter pea cv. Maksimirski rani in a mixture with wheat cv. Sana. Just before sowing, pea seeds were inoculated with the strain Rhizobium leguminosarum bv. viciae 1001 from the microbial collection of the Department of Microbiology, Faculty of Agriculture, University of Zagreb. The highest number of root nodules (43 nodules/plant), as well as the highest nodule mass (0.219 g/plant-1) were determined in the inoculated variant. The highest number of pods (19.0) and seeds per plant (60) were determined in the inoculated variant as well. The highest 1000-seed mass (132 g) and seed mass per plant (7.93 g) were also determined in the inoculated variant. Average pea seed yield ranged from 2949 kg ha-1 (control) up to 3353 kg ha-1 (inoculation). The conclusion of this research is that the highest seed (3353 kg ha-1) and crude protein yields (833 kg ha-1) were obtained with inoculated forage winter pea cv. Maksimirski rani. Seed inoculation of the studied pea cultivar Maksimirski rani with the strain Rhizobium leguminosarum bv. viciae 1001 influenced also higher milk production per hectare compared to the control and the nitrogen top-dressed variant.